Bookshop dog (The) - Rylant, Cynthia (New York : The Blue Sky Press, 1996)
When Martha Jane's owner falls ill and has to go to the hospital, the inhabitants of her small town bicker over who will care for the beloved dog.
Keywords: Dogs-Fiction; Neighborliness-Fiction